KEY FACTORS FOR SUSTAINABLE RATIONAL USE OF MEDICINE PROGRAM IN GUNUNGKIDUL AND SLEMAN DISTRICTS, INDONESIA - H, Sunartono; Ys, Prabandari; H, Kusnanto; S, Suryawati (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Many of the rational use of medicines (RUM) interventions have been proven effective in improving medicine use, but the impacts were usually not sustainable for longer period of time. Gunungkidul and Sleman Districts of Indonesia have succeeded in implementing RUM program for more than two decades. This is considered rare, and therefore, it is important to identify factors contributing to the success. Methods: This is a single case study with non-experimental exploratory design. Quantitative and qualitative data were collected integratively to obtain information concerning the indicators and the process of RUM implementation. Quantitative data were collected in reference to the World Health Organization (WHO) 1993 RUM indicators, including average number of medicines per prescription (polypharmacy), percentage of patients receiving antibiotics, and percentage of patients receiving injections. Qualitative data were analyzed descriptively and were arranged chronologically in respective to each district. Results: Implementation of RUM in the two districts has successfully lasted up to 20 years. The annual medicine use indicators from 1994 to 2014 in Gunungkidul District show that polypharmacy decreased from 4.2 to 2.89, percentage patients receiving injections declined from 68.05% to 0%, and percentage of patients receiving antibiotics improved from 52.1% to 24.1%. The same indicators in Sleman District show that, between 1998 and 2014, polypharmacy remained stable at 3, percentage of patients receiving injections declined from 4.9% to 0.18%, and percentage of patients receiving antibiotics improved from 44.31% to 20%. Culturization of RUM program is the main key for sustainable impacts. Another important key is the high commitment of health policymakers to implement the principles of evidence-based treatment. Conclusions: The culturization of RUM program followed by continuous monitoring and evaluation by district health managers were the key factors to maintain the impact of the intervention.